Computer-measuring system of the induction motor’s dynamical torque-speed characteristics - V.Yu. Kucheruk; I.P. Kurytnik; Ye.Z. Oshanov; P.I. Kulakov; A.A. Semenov; D.Zh. Karabekova; A.K. Khassenov (Қарағанды университетінің хабаршысы. Физика сериясы)
In the article an efficient method of determining the dynamic torque-speed characteristic of induction motors and the computer-measuring system for its realization is considered. In this method, the additional flywheel is used, the dynamic measurements of the angular speed as a function of time are taken at the start, after the end of the transition process, and at during the self-braking mode of the induction motor. For approximating the data that are obtained as a result of the measurements, the moving average algorithm is used. Also, with the help of this system, the inertia moment, angular speed dependence on time, electromagnetic dynamic moment dependence on time, electromagnetic dynamic power dependence on time, mechanical dynamic power dependence on time, and dynamic loss in rotor winds dependence on time are measured. In the article, the results of experimental measurements of the induction motor characteristics using a proposed computermeasuring system are given. The proposed system is experimental; in the future, it can be used to test induction motors during their production processes.